Learning Game Application Development: Crime Scene Investigation (CSI) - Erika Ramadhani (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Digital forensic learning media has been developed as a computer-based application. The development of game-based applications that can be used to improve cognitive learning outcomes has been tested over a period of time. The research was conducted using the ADDIE research and development method. The ADDIE method consists of five stages, namely analysis, design, development, implementation, and evaluation. The purpose of the study was to find out if this software has been successfully developed and whether it is a useful learning tool for digital forensics.